2017
DOI: 10.1515/bmt-2015-0139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface modification of zirconia on cell adhesion, metabolic activity and proliferation of human osteoblasts

Abstract: Titanium dental implants with sandblasted and/or acid-etched surfaces have shown clinical superiority in comparison to their smooth, machined counterparts, and are now state of the art. Sandblasting of finished, sintered zirconia implants, however, will damage the surface structure and affect the mechanical properties. To improve osseointegration of zirconia dental implants without impairing the original mechanical strength by crack initiation and partial phase transformation from tetragonal to monoclinic, rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 34 publications
0
32
0
2
Order By: Relevance
“…29,30 Surface roughness increased cell attachment owing to its increased protein absorption. 31 In addition, research has shown that HA has good biocompatibility and bioactivity, 32 and PDA improves the bioactive behavior of materials owing to its catecholamine structure. 33 Therefore, it was suggested that the mechanism of positive response of C3H10T1/2 cells to the HA and PDA coatings could be attributed to the change in the surface chemistry and improvement in hydrophilicity and surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Surface roughness increased cell attachment owing to its increased protein absorption. 31 In addition, research has shown that HA has good biocompatibility and bioactivity, 32 and PDA improves the bioactive behavior of materials owing to its catecholamine structure. 33 Therefore, it was suggested that the mechanism of positive response of C3H10T1/2 cells to the HA and PDA coatings could be attributed to the change in the surface chemistry and improvement in hydrophilicity and surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Early zirconia implants had macro‐ and microscopic surface characteristics that resulted in inferior osseointegration and removal torques, and their fracture rates were too high as well (Gahlert et al, ; Sennerby, Dasmah, Larsson, & Iverhed, ; Thoma et al, ). Following recent advances in fracture tolerance, flexural strength, and hardness (Becker et al, ; Hashim, Cionca, Courvoisier, & Mombelli, ), manufacturers seem to have overcome these issues and today recommend similar surgical and restorative protocols with zirconia as with titanium implants (Al Qahtani et al, ; Bubik et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…45,46,49 Likewise, differences in mammalian cellular growth on smooth surfaces (polished) as opposed to rougher ones (sandblasted and/or acid-etched) have been debated in the literature. [50][51][52] In particular, greater osteoblast proliferation has been observed on rougher cpTi and ZrO 2 surfaces as opposed to their smoother counterparts. 50,51 On the other hand, broblasts and preosteoblasts have been shown to grow equally well on ZrO 2 and cpTi substrates in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52] In particular, greater osteoblast proliferation has been observed on rougher cpTi and ZrO 2 surfaces as opposed to their smoother counterparts. 50,51 On the other hand, broblasts and preosteoblasts have been shown to grow equally well on ZrO 2 and cpTi substrates in vitro. [52][53][54][55] Based on the ndings of these previous studies, the trends in terms of oral bacterial adhesion and mammalian cellular proliferation on various surface-modied cpTi and ZrO 2 appear to be inconclusive.…”
Section: Introductionmentioning
confidence: 99%